Navigating an Identity Playground: Using sociomateriality to build a theory of identity play. Issue 1 (January 2022) - Stanko, Taryn Lyn; Dahm, Patricia Caulfield; Lahneman, Brooke; Richter, Jonathon
The construct of identity play, which involves the exploration and experimentation with possible future selves, is underexplored in organizational literature. To extend theory on identity play, we take a narrative inquiry approach and examine qualitative interview data in the context of virtual environments. Using a sociomateriality perspective, we contribute to theory on identity play in three ways. First, we reveal how identity play unfolds via the sociomaterial intertwining of not just human agency, but also material agency, situated work practices, and self-representations. Second, we offer a new definition of identity play that goes beyond the exploration of possible selves and uncover identity play narratives on the possible self, the improbable self, and the impossible self. We demonstrate how identity play, particularly with impossible selves, shapes others ' experiences and thus has implications beyond the self. Finally, three identity play affordances emerged: plasticity of appearance, plasticity of behavior, and plasticity of perspective.